Proses Berpikir Kritis dalam Memecahkan Masalah Terbuka Berbasis Polya Sub Pokok Bahasan Persegi Panjang dan Persegi Siswa Kelas VII-B SMP Negeri 10 Jember - Palupi, Doni Dwi; Sugiarti, Titik; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research is a qualitative decriptive research. The study was conducted on 36 students of class VII B SMP Negeri 10 Jember. This study aims to determine the level of critical thinking and critical thinking process of students in solving mathematical problems based on polya. Grouping is based on Polya's breaking step and students' critical thinking skills in open math problem solving. From the results of research at the stage of understanding the problem students with the uncritical category (S1) is only able to do one problem only and for other problems S1 can only write down what is known and asked in the matter. Students with the category of less critical (S2) able to understand and explain the problem well and can prepare a plan of completion.Students with moderately critical category (S3) are able to solve the problem correctly. Students with the critical category (S4) are able to solve the problem and draw conclusions correctly. Students with category (S5) mapu solve all problems appropriately. S5 is able to use other ways or alternatives in solving problems with correct answers. Keywords: Critical thinking, Polya’s problem solving, Process of critical thinking, Level of critical thinking